2005
DOI: 10.1065/espr2005.08.283
|View full text |Cite
|
Sign up to set email alerts
|

Safety Evaluation for a Biodiesel Process Using Prion-Contaminated Animal Fat as a Source (6 pp)

Abstract: The obtained results indicated that biodiesel produced from prion-contaminated fat was safe under the tested process conditions. However, it has to be pointed out that the results cannot be generalized because a different process control using other conditions may lead to different results and then has to be analysed independently. It is clear that the production of biodiesel from high risk material represents a more economic usage than the combustion of such material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…Our biochemical results are comparable to previous studies, at least with regards to the biodiesel and glycerol phase [15]. Biodiesel and glycerol products had no detectable infectivity in our long term animal assay (survival>200d).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our biochemical results are comparable to previous studies, at least with regards to the biodiesel and glycerol phase [15]. Biodiesel and glycerol products had no detectable infectivity in our long term animal assay (survival>200d).…”
Section: Discussionsupporting
confidence: 90%
“…Production of biodiesel from animal fat has been proposed to decontaminate any potential prion infectivity present in the biodiesel [15]. Production of biodiesel from MBM can produce a valuable fuel and a nutritious solid MBM residue that could be used as feed additive.…”
Section: Introductionmentioning
confidence: 99%
“…Diesel exhaust is believed to consist of thousands of organic constituents and is a major cause of urban pollution (Bayona et al 1988;Draper 1986;Erdinger et al 2005;Mestres 2005;Morville 2006;Ona 2006;Schuetzle 1983;Schuetzle & Lewtas 1986;Seidel et al 2006). A number of studies on the adverse effects of diesel exhaust particles (DEP) on human health, including lung cancer (McClellan 1987;Ichinose et al 1997), allergic rhinitis (Muranaka 1986;Takafuji et al 1987), bronchial asthma-like disease (Sagai et al 1996;Miyabara et al 1998), and disruption of endocrine function, have been reported (Yoshida et al 1999;Watanabe & Oonuki 1999;Tsukue et al 2001Tsukue et al , 2002.…”
Section: Introductionmentioning
confidence: 99%
“…Repeated reverse-phase chromatography resulted in the successful isolation of several acidic substances including the new vasodilative materials, 4-hydroxy-3-nitrobenzoic acid and 3-hydroxy-4-nitrobenzoic acid. Seidel et al 2006). A number of studies on the adverse effects of diesel exhaust particles (DEP) on human health, including lung cancer (McClellan 1987;Ichinose et al 1997), allergic rhinitis (Muranaka 1986;Takafuji et al 1987), bronchial asthma-like disease (Sagai et al 1996;Miyabara et al 1998), and disruption of endocrine function, have been reported (Yoshida et al 1999;Watanabe & Oonuki 1999;Tsukue et al 2001Tsukue et al , 2002.…”
mentioning
confidence: 99%
“…Diesel exhaust is believed to consist of thousands of organic constituents and is a major cause of urban pollution (Bayona et al 1988;Draper 1986;Erdinger et al 2005;Mestres 2005; Morville et al 2006;Ona et al 2006;Schuetzle 1983;Schuetzle and Lewtas 1986;Seidel et al 2006). A number of studies on the adverse effects of diesel exhaust particles (DEP) on human health, including lung cancer (McClellan 1987;Ichinose et al 1997), allergic rhinitis (Muranaka et al 1986;Takafuji et al 1987), bronchial asthma-like disease (Sagai et al 1996;Miyabara et al 1998), and disruption of endocrine function, have been reported (Yoshida et al 1999;Watanabe and Oonuki 1999;Tsukue et al 2001Tsukue et al , 2002.…”
Section: Introductionmentioning
confidence: 96%